Analisis Kemampuan Literasi Sains Peserta Didik Kelas VIII SMP Terakreditas A se-Kecamatan Mamajang Ditinjau dari Gender - Adiba Nugraharis; Salma Samputri; Nurhayani H. Muhiddin (Universitas Negeri Makassar, 2025)
This study aims to determine the level of science literacy ability in aspects of context, competence and knowledge of grade VIII students of A-accredited junior high school in Mamajang sub-district in terms of gender. The sample selected used the Slovin formula so that the sample in this study was 303 students. The research instrument consists of 30 multiple-choice questions. Based on the results of data analysis, it is known that science literacy in the aspects of context, competence, and knowledge of grade VIII students of A-accredited junior high schools in Mamajang sub-district in terms of gender, namely in the context aspect and competency aspects of female students has a higher percentage compared to male students, but in the aspect of knowledge male students have a higher percentage compared to female students. The average score in female students is 13 with the medium category, in male students it has a score of 11 with the low category, this shows that female students have better science literacy skills than male didk participants, although in the aspect of knowledge and male students have a higher percentage.